Design and Implementation of RFID Active Tags and Mutual Authentication Protocol with Ownership Transfer Stage - Hussein, Issam A.; Ali, Ramzy S.; Jasim, Basil H. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
Radio frequency identification (RFID) technology is being used widely in the last few years. Its applications classifies into auto identification and data capturing issues. The purpose of this paper is to design and implement RFID active tags and reader using microcontroller ATmega328 and 433 MHz RF links. The paper also includes a proposed mutual authentication protocol between RFID reader and active tags with ownership transfer stage. Our protocol is a mutual authentication protocol with tag’s identifier updating mechanism. The updating mechanism has the purpose of providing forward security which is important in any authentication protocol to prevent the attackers from tracking the past transactions of the compromised tags. The proposed protocol gives the privacy and security against all famous attacks that RFID system subjected for due to the transfer of data through unsecure wireless channel, such as replay, denial of service, tracking and cloning attacks. It also ensures ownership privacy when the ownership of the tag moves to a new owner.